Design and Study of a Miniaturized Millimeter Wave Array Antenna for Wireless Body Area Network. (9th May 2022) - Alharbi, Abdullah G.; Rahman, H. M. Arifur; Khan, Mohammad Monirujjaman; Abbasi, Muhammad Inam; Albraikan, Amani Abdulrahman; Almalki, Faris A.
Abstract : A miniaturized millimeter wave (mmWave) antenna for wireless body area networks is proposed in this paper. The antenna is found to be operational in the V-band, around the 60 GHz frequency range, with high efficiency of up to 99.98% in free space simulations. A multilayer, thin substrate was implemented in the design to enhance radiation efficiency and gain. The antenna seems to be most suitable for small electronic devices and wireless body area network (WBAN) applications because of its low profile and lighter weight concept. To enhance its performance, several arrays of different orders were created. The Parallel-Fed and Tapered Feed Line methods were followed to design the planar arrays with 1 × 2, 1 × 4, and 2 × 2 elements in the primary design. Free space results were compared, and a 2 × 2 element array was found to be the most balanced according to the simulations. To justify the eligibility of these designs for WBAN applications, a virtual human body model was created within the 3D computer-simulated environment and the simulations were repeated, where four equal-spaced distances were taken into account to identify the antenna and its array behavior more accurately. Simulations returned optimistic results for the 2 × 2 element planar array arrangement in almost all parameters, even when placed close to the human body at any distance greater than 2 mm.